2022
DOI: 10.3389/fnut.2022.963413
|View full text |Cite
|
Sign up to set email alerts
|

Biopolymeric nanoparticles based effective delivery of bioactive compounds toward the sustainable development of anticancerous therapeutics

Abstract: Nowadays, effective cancer therapy is a global concern, and recent advances in nanomedicine are crucial. Cancer is one of the major fatal diseases and a leading cause of death globally. Nanotechnology provides rapidly evolving delivery systems in science for treating diseases in a site-specific manner using natural bioactive compounds, which are gaining widespread attention. Nanotechnology combined with bioactives is a very appealing and relatively new area in cancer treatment. Natural bioactive compounds have… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 79 publications
0
21
0
Order By: Relevance
“…Nanocarriers have traditionally been designed to be selectively entrapped and accumulated around tumor cells and tumor microenvironments within tumor tissues via the EPR effect or release drugs safely and specifically to those cells to increase the bioavailability of the drug while minimizing off-target effects on normal tissues [ 48 , 49 , 50 , 51 , 52 , 53 , 56 , 58 ]. Loading CZ into PLGA-NPs may improve the solubility of poorly water-soluble CZ during systemic delivery and is useful for sustained and controlled CZ release over days, weeks, or months as a stable form, leading to a longer circulation time compared to that of conventional devices.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…Nanocarriers have traditionally been designed to be selectively entrapped and accumulated around tumor cells and tumor microenvironments within tumor tissues via the EPR effect or release drugs safely and specifically to those cells to increase the bioavailability of the drug while minimizing off-target effects on normal tissues [ 48 , 49 , 50 , 51 , 52 , 53 , 56 , 58 ]. Loading CZ into PLGA-NPs may improve the solubility of poorly water-soluble CZ during systemic delivery and is useful for sustained and controlled CZ release over days, weeks, or months as a stable form, leading to a longer circulation time compared to that of conventional devices.…”
Section: Resultsmentioning
confidence: 99%
“…More importantly, NPs can significantly improve the aqueous solubility and, eventually, the oral bioavailability of poorly soluble drugs due to a smaller size, greater surface area to volume ratio, and higher cell penetration ability [ 48 , 54 , 55 ]. Currently, several efforts to design systematic formulations to overcome the poor solubility of hydrophobic TKIs have demonstrated that different polymeric nanocomplex NPs significantly improve the anti-cancer efficacy of TKIs, such as sorafenib, ponatinib, and nilotinib, by enhancing their bioavailability and allowing for the efficient delivery of the drug to tumor tissues while reducing adverse side effects [ 48 , 49 , 50 , 51 , 52 , 53 , 56 , 57 , 58 , 59 , 60 , 61 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations